Preparation of Financial Statements Based on Financial Accounting Standards for Micro, Small and Medium Entities - Isna Ardila; Rezki Zurriah; Yani Suryani (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2019)
This research aims to produce a financial report of micro Small and medium enterprises (MSMES) based financial accounting standards of Micro small entity (SAK EMKM). This objective is based on existing conditions where SMES activities are running without relying on the information of financial statements that are arranged in an orderly and orderly manner based on standards. This type of research is qualitative research. This research uses primary and secondary data types. The sample used in this study was the SMES of the TELKOM Community Development Center Partnership and Community Development Program Unit for a similar food industry sector. The results showed that the financial statements were prepared through the stages of recording financial transactions and summarizing. Financial statements based on SAK EMKM compiled consist of statements of financial position, income statement, and notes to financial statements.